AUDITOR SIZE, AUDIT COMMITTEE, MANAGERIAL AND INSTITUTIONAL OWNERSHIP TOWARD EARNINGS MANAGEMENT OF SHARIA BANKS IN INDONESIA - Maghfuriyah, Alfi (Jaksya: Jurnal Akuntansi Syariah, 2024)
This research aimed to examine the influence of auditor size, audit committee, managerial, and institutional ownership on earnings management practices in sharia commercial banks in Indonesia. The study utilized secondary data from the annual financial reports of sharia banks published between 2020 and 2024. The sampling technique used was purposive sampling, involving a sample from six years of financial statements from 10 sharia banks. Earnings management was proxied by discretionary accruals adapted to the characteristics of the banking sector. The determination of the earnings management coefficient was done by regressing total accruals calculated using the Beaver and Engel model. The influence of auditor size, audit committee, managerial ownership, and institutional ownership on earnings management was tested using multiple regression analysis. The research period showed that the variables and data were normally distributed. Classic assumption tests, including multicollinearity, heteroscedasticity, and autocorrelation tests, indicated no violations, confirming that the data met the conditions for using the multiple linear regression model. The results revealed that auditor size has a positive but insignificant influence on earnings management, while managerial ownership has a negative but insignificant influence. In contrast, the audit committee and institutional ownership variables negatively and significantly influenced earnings management.